2016
DOI: 10.1002/hyp.10906
|View full text |Cite
|
Sign up to set email alerts
|

The June 2013 Alberta Catastrophic Flooding Event: Part 1—Climatological aspects and hydrometeorological features

Abstract: In June 2013, excessive rainfall associated with an intense weather system triggered severe flooding in southern Alberta, which became the costliest natural disaster in Canadian history. This article provides an overview of the climatological aspects and large-scale hydrometeorological features associated with the flooding event based upon information from a variety of sources, including satellite data, upper air soundings, surface observations and operational model analyses. The results show that multiple fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 42 publications
3
48
0
Order By: Relevance
“…An upper ridge is observed to the east of the trough extending from central Alaska toward the U.S. Great Plains. The locations of the upper trough and ridge are consistent with the evolution of the system discussed in Liu et al (2016). The simulation also captures observed strong jets upstream and downstream of the trough.…”
Section: A Event Description and Synoptic Developmentssupporting
confidence: 79%
See 4 more Smart Citations
“…An upper ridge is observed to the east of the trough extending from central Alaska toward the U.S. Great Plains. The locations of the upper trough and ridge are consistent with the evolution of the system discussed in Liu et al (2016). The simulation also captures observed strong jets upstream and downstream of the trough.…”
Section: A Event Description and Synoptic Developmentssupporting
confidence: 79%
“…It was found that a train of Rossby waves across the North Pacific Ocean helped to form a blocking pattern in the northeastern North Pacific. A detailed analysis of the evolution of weather patterns during the heavy precipitation period can be found in Liu et al (2016). It was shown that a slow-moving upper low with an associated surface low pressure system moved into southern Alberta, which, combined with terrain effects, brought continuous precipitation during the period 19-21 June 2013, especially over the foothills and mountains.…”
Section: A Event Description and Synoptic Developmentsmentioning
confidence: 99%
See 3 more Smart Citations